Political participation of refugees as a means to realise the right to repatriation : the search for a durable solution to the refugee problem in Africa - Van Reenen, Tobias P. (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2006.